Design of a SDR ground station for Low-orbit satellites (2021)
Space systems are characterized by the planning and creation of all their segments in order for a mission to be accomplished together; regarding these systems, two space missions have been developed in Colombia: Libertad 1, a 1U CubeSat from Sergio Arboleda University and FACSAT1, a 3U CubeSat from the Colombian Air Force. These missions generated the complete development of the space segment called satellite, in turn they have generated the terrestrial segment called ground station. In order to ensure the success of any mission, it is necessary to have control over the development of the ground segment, it does it mean, the ground stations; for this reason, and being motivated in this segment at the Fundación Universitaria Los Libertadores, it was possible to define a preliminary design to track pico and nano satellites within the amateur or university segment. Based on applied research, the generation of knowledge was sought within the institution with its application in the space sector, developing the necessary guidelines that would allow the identification of the different components for the construction of an Earth Station for small satellites. With the search for the necessary capacities to obtain an adequate reception of the satellites, a low-cost earth station was obtained using commercial technology and mainly hardware components of the SDR type. Finally, a comparison was made with low cost earth stations to look at the contribution in Colombia.